A Thermodynamic Framework for Stretching Processes in Fiber Materials - Arango-Restrepo, A.; Rubi, J. M.; Pradhan, Srutarshi (Frontiers in Physics, 2021)
A fibre breakage process involves heat exchange with the medium and energy dissipation in form of heat, sound and light, among others. A purely mechanical treatment is therefore in general not enough to provide a complete description of the process. We have proposed a thermodynamic framework able to identify new alarming signals before the breaking of the fibres. The occurrence of a maximum of the reversible heat, a minimum of the derivative of the dissipated energy or a minimum in the stretching velocity as a function of the stretch can prevent us from an imminent breakage of the fibres which depends on the nature of the fibres material and on the load applied. The general framework proposed can be used to analyse how dissipation and thermal fluctuations affect the stretching process of fibres in systems as diverse as single-molecules, textil and muscular fibres and composite materials.